Pengembangan E-Modul Terintegrasi Quizizz untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik Kelas VIII di SMP Negeri 1 Cina - Nurmawati, Nurmawati (Jurnal Ilmiah Kanderang Tingang, 2025)
. Development research has been carried out which aims to produce an integrated quizizz e-module to improve the critical thinking skills of class VIII students at SMP Negeri 1 Cina. This research analyzes the validity of the Quizizz integrated e-module developed. Apart from analyzing responses from practitioners or teachers to the Quizizz integrated e-module that was developed, it also analyzes the effectiveness of the Quizizz integrated e-module on students' critical thinking abilities. The research was carried out in class VIII A of SMP Negeri 1 Cina, with a total of 26 students. Validation analysis in this research uses the Aiken's V index and uses N-Gain value analysis to determine the increase in students' abilities after implementing Quizizz integrated e-module learning. Based on research and data analysis, it can be concluded that the Quizizz integrated e-module, both in terms of material and media, obtained valid results by both experts. Practitioner assessments of the Quizizz integrated e-module were very good. So the Quizzizz integrated e-module is suitable for use. In its application, there was an increase in the critical thinking skills of students in class VIII A of SMP Negeri 1 Cina. So the Quizizz integrated e-module is quite effective to use.